Altered Viral Replication and Cell Responses by Inserting MicroRNA Recognition Element into PB1 in Pandemic Influenza A Virus (H1N1) 2009 - Xiaoyue Shen; Wenkui Sun; Yi Shi; Zheng Xing; Xin Su (Mediators of Inflammation)
Objective. MicroRNAs (miRNAs) are endogenous noncoding RNAs that spatiotemporally modulate mRNAs in a posttranscriptional manner. Engineering mutant viruses by inserting cell-specific miRNA recognition element (MRE) into viral genome may alter viral infectivity and host responses in vital tissues and organs infected with pandemic influenza A virus (H1N1) 2009 (H1N1pdm). Methods. In this study, we employed reverse genetics approach to generate a recombinant H1N1pdm with a cell-specific miRNA target sequence inserted into its PB1 genomic segment to investigate whether miRNAs are able to suppress H1N1pdm replication. We inserted an MRE of microRNA-let-7b (miR-let-7b) into the open reading frame of PB1 to test the feasibility of creating a cell-restricted H1N1pdm virus since let-7b is abundant in human bronchial epithelial cells. Results. miR-let-7b is rich in human bronchial epithelial cells (HBE). Incorporation of the miR-let-7b-MRE confers upon the recombinant H1N1pdm virus susceptibility to miR-let-7b targeting, suggesting that the H1N1pdm and influenza A viruses can be engineered to exert the desired replication restrictive effect and decrease infectivity in vital tissues and organs. Conclusions. This approach provides an additional layer of biosafety and thus has great potential for the application in the rational development of safer and more effective influenza viral vaccines.